Content Analysis of School Textbooks on Chemistry Bond Materials Viewed from Chemical Representation Criteria - Luthfiana, Eva; Raharjo, Sentot Budi; Vh, Elfi Susanti; Indriyanti, Nurma Yunita (PAEDAGOGIA, 2019)
The purpose of this study was to evaluate the chemical representation of chemical bonds in three chemical textbooks. Chemical studies are basically related to three types of chemical representations: macro, submicro and symbolic. In this study a detailed review was carried out and could define the chemical representations in school textbooks to improve students' understanding of chemistry. A detailed analysis reveals five criteria for evaluating chemical representations which are included in three detailed chemical textbooks revealing five criteria for evaluating the chemical representation used in school textbooks. These criteria (C1-C5) are: (C1) type of representation; (C2) interpretation of surface features; (C3) their relationship with the text; (C4) the existence and characteristics of a statement; (C5) the level of correlation between components consisting of several representations. The five criteria include the basic elements needed to utilize chemical representations that are better in understanding chemistry. These five criteria can also be used for analysis of existing school textbooks and as a tool for authors in designing new chemistry textbooks